Pola Pendidikan Aqidah Akhlak TPA Al-Abrar pada Santri Kuta Malaka Aceh Besar - Zainuddin T (Khulasah : Islamic Studies Journal, 2026)
This study examines the patterns of aqidah and akhlak education at TPA Al-Abrar in Kuta Malaka Subdistrict, Aceh Besar Regency, to foster young students' understanding of Islamic beliefs and noble morals. Employing a qualitative descriptive approach with data collection via observation, interviews, and documentation, the research identifies key patterns including teacher exemplification, delivery of aqidah-akhlak materials, habituation of daily prayers, and reward-based evaluation. Supporting factors include parental involvement and student enthusiasm, while obstacles involve social media influence and insufficient home guidance. These patterns effectively shape students' moral character, requiring ongoing collaboration between TPA and families